THE IMPACT OF MATERNAL OBESITY ON PREGNANCY – A REVIEW ARTICLE - Ilieva, Maja Pejkovska (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Maternal obesity has been estimated as a global epidemic, affecting 40% of pregnant women in developed nations. The weight of females that are pregnant has become one of the most concerning points in the modern obstetrics. For this matter after consulting the most accurate literature from academic books in the field and from internet sources from the year 2020 until the year 2025 available on PubMed, Scopus, Data of Science, Google Scholar, ResearchGate, Academia and others we have created a review article that takes in consideration the impact of maternal obesity on the pregnancy itself. Women may have been obese before becoming pregnant or they may have rapidly gained weight during pregnancy and the types of maternal obesity have their challenges for the pregnancy outcome. The maternal obesity must be carefully treated since it is directly responsible for the impact on gestational diabetes mellitus (GDM), hypertensive disorders, and various perinatal complications. By analyzing the types of maternal obesity and complications that occur during pregnancy we take care not only for the current health of the pregnant mothers and their babies but also of their future to take preventive measures, lifestyle changes and thus to improve their health and the health of their babies. Key words: maternal obesity, pregnancy outcome, diabetes mellitus, hypertension, perinatal complications.